Pengaruh Pengembangan Karir, Kepuasan Kerja Dan Kompensasi Terhadap Retensi Karyawan Di PT. Intracawood Cabang Tarakan - Antik Trivosa Anggraeni Bate; Awan Santosa (Economic Reviews Journal, 2025)
This study aims to analyze the influence of career development, job satisfaction and compensation on employee retention. The sample in this study was 55 respondents who worked at PT. Intracawood Tarakan Branch. The data collection technique used was a survey method with the research instrument used being a questionnaire. The results of the instrument test stated that the data in this study were proven to be valid and reliable. The classical assumption test stated that the data in this study were normally distributed and produced a regression model that was free from multicollinearity and heteroscedasticity. The results of this study prove that: (1) Career development values ​​have a significant positive effect on employee retention, (2) Job satisfaction values ​​have a significant positive effect on employee retention and (3) Compensation values ​​have a significant positive effect on employee retention. These results have implications for further researchers to study the field of HR management, especially regarding employee retention. The findings of this study have implications for PT. Intracawood to formulate career development strategies, job satisfaction and compensation in order to influence employee retention.